Experimental investigation of arc column expansion generated by high-energy spark ignition system - Korytchenko, K.V.; Kasimov, A.M.; Golota, V.I.; Ajmani, S.; Dubinin, D.P.; Meleshchenko, R.G. (Вопросы атомной науки и техники, 2018)
The results of an experimental investigation of an improved spark-capacitor ignition system are presented. The high-speed shooting and oscillography techniques were used. Influence of the ignition system parameters on a size of an ignition region, a time scale of spark energy input and discharge efficiency has been found out. The reason of the high spark efficiency has been explained. Variants of circuit diagrams generating a single arc pulse and double arc pulse have been tested.